Differences in anthropometric characteristics and motor abilities of professional football players from leading and average teams in Serbian super league - Radivoje Radakovic; Branislav Majkic; Borko Katanic; Karuppasamy Govindasamy; Aleksandra Aleksic Veljkovic; Alexandru Ioan Băltean; Vlad Adrian Geantă (BMC Sports Science, Medicine and Rehabilitation)
Abstract Aim of study The aim of the study was to examine the differences between professional football players from leading and average teams in anthropometric characteristics and motor abilities. The sample of participants included 55 professional football players from the Serbian Super League, the top-tier national football competition. Methods The sample was divided into players representing the leading team (LT; n = 29) and the average team (AT; n = 26) in the Serbian championship. A total of 16 parameters were measured, including 5 anthropometric parameters and 11 variables of motor abilities, assessing sprint and acceleration performance, agility, explosive power, and endurance. Based on the independent t-test, it was determined that the leading team has a significantly lower fat percentage (0.016) compared to players from the average team. Results Regarding motor abilities, a difference has been observed on the side of the LT compared to AT in sprint performance, such as 20 m (0.001), and 30 m sprint (0.005), as well as acceleration index 10/20m (0.006). However, in contrast, the AT achieved better results in agility zig-zag (0.000) and zig-zag with a ball test (0.000), as well as index zig-zag (0.038). Additionally, the AT had better results in the test of explosive lower extremity power - CMJ (0.005). There were no differences between players in other anthropometric and motor performances. Conclusions These findings suggest that while the leading team demonstrates superior sprinting and acceleration capabilities, the average team excels in agility and explosive power of the lower extremities. Although certain differences in anthropometric characteristics and motor abilities were observed between the LT and AT groups of football players, further research is needed to examine these differences in more detail and provide a more comprehensive understanding.